2008
DOI: 10.1111/j.0030-1299.2008.16611.x
|View full text |Cite
|
Sign up to set email alerts
|

Host plant quality and defence against parasitoids: no relationship between levels of parasitism and a geometrid defoliator immunoassay

Abstract: Host plant quality has a major influence on the performance, and ultimately on the fitness of an herbivorous insect, but may also have indirect effects on the third trophic level by affecting an herbivore's defensive ability against natural enemies. In a three-year field study, we examined the effects of natural food quality on the ability of autumnal moths, Epirrita autumnata (Lepidoptera, Geometridae), to defend themselves against parasitoids. In each year, we confirmed the variation in quality of host trees… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(45 citation statements)
references
References 49 publications
0
45
0
Order By: Relevance
“…3). The larval and pupal parasitoid species of this study correspond to the parasitoid fauna found during the latest increase and peak phases of the cycle (Klemola et al 2007, Klemola, N. et al 2008 and are listed in Table 2.…”
Section: Larval and Pupal Parasitismmentioning
confidence: 99%
See 1 more Smart Citation
“…3). The larval and pupal parasitoid species of this study correspond to the parasitoid fauna found during the latest increase and peak phases of the cycle (Klemola et al 2007, Klemola, N. et al 2008 and are listed in Table 2.…”
Section: Larval and Pupal Parasitismmentioning
confidence: 99%
“…We tested our hypothesis on reversed effects of specialist and generalist natural enemies with one-year field experiments on the larval and pupal stages, which seem most prone to mortality from natural enemies (Tanhuanpää et al 1999, 2001, Klemola, N. et al 2008, Hansen et al 2009). Specifically, we estimated the probability of larval and pupal parasitism, as well as pupal predation of both species by vertebrates and invertebrates, under field conditions in 2007.…”
mentioning
confidence: 99%
“…In post-peak and decline phases of the autumnal moth cycle, the overall larval parasitism rates are noticeably high, occasionally approaching 100%, of which a major proportion (>90%) can be caused by solitary parasitoids (Bylund, 1995;Tanhuanpää et al, 2002;Klemola et al, 2007Klemola et al, , 2008aK. Ruohomäki and T. Klemola, unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…Klemola et al, unpublished data). The parasitism rate ranges from 0 to 100 (Bylund, 1995;Klemola et al, 2008a). For 5th instar larvae of the autumnal moth, the value a is the total amount of leaves consumed by a non-parasitised larva, while b is the total amount of leaves eaten by a parasitised individual.…”
Section: Mathematical Modellingmentioning
confidence: 99%
See 1 more Smart Citation